Analisis Penerapan Psak No 102 Tentang Akuntansi Murabahah (Studi Kasus pada BMT Ar-Raudhatul Hasanah Medan) - Damayanti, Putri Merry; K, Kusmilawaty (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to determine the suitability of murabahah accounting treatment regarding recognition, measurement, presentation and disclosure at BMT Ar-Raudhatul Hasanah Medan in order to increase professionalism and trust in the public that the implementation of murabahah transactions is in accordance with established accounting standards. The source of data obtained is primary data. In this research, data was obtained from informants by means of direct interviews with parties who understand the application of murabahah accounting at BMT Ar-Raudhatul Hasanah Medan. The results of the research show that the application of PSAK No. 102 to BMT Ar-Raudhatul Hasanah in terms of profit measurement, the murabahah contract process is in accordance with PSAK 102. However, in terms of presentation, recognition and disclosure, it is not in accordance with PSAK 102. Where in terms of presentation there has been no recording. presented in relation to the purchase of goods on a wakalah basis, in terms of recognition, namely not recognizing the existence of murabahah asset inventory and not recognizing murabahah profits (margin) at the beginning of the contract, as well as in terms of disclosure of the amount of receivables to be borne by the partner (customer) not being disclosed at the beginning of the contract. Therefore, it can be suggested that BMT Ar-Raudhatul Hasanah Medan is expected to be able to carry out recording activities and prepare financial reports in accordance with applicable PSAK Syariah standards in order to maintain a sense of trust in partners (customers).